Hospital end-of-life care: Families' free-text notes - Kurkowski, Sandra; Radon, Johannes; Vogt, Annika R.; Weber, Martin; Stiel, Stephanie; Ostgathe, Christoph; Heckel, Maria (BMJ Supportive & Palliative Care, 2020)
Background: Palliative care strives to improve quality of life for patients with incurable diseases. This approach includes adequate support of the patients' loved ones. Consequently, loved ones have personal experiences of providing end-of-life care for their next. This is a resource for information and may help to investigate the loved ones' perspectives on need for improvements. Aim: To identify further quality aspects considered important by loved ones to improve the quality of care at the end of life as an addition to quantitative results from the Care of the Dying Evaluation for the German-speaking area (CODE-GER) questionnaire. Design: Within the validation study of the questionnaire â € Care of the Dying Evaluation' (CODETM) GER, loved ones were asked to comment (free text) in parallel on each item of the CODE-GER. These free-text notes were analysed with the qualitative content analysis method by Philipp Mayring. Setting/participants: Loved ones of patients (n=237), who had died an expected death in two university hospitals (palliative and non-palliative care units) during the period from April 2016 to March 2017. Results: 993 relevant paragraphs were extracted out of 1261 free-text notes. For loved ones, important aspects of quality of care are information/communication, respect of the patient's and/or loved one's will, involvement in decision-making at the end of life (patient's volition) and having the possibility to say goodbye. Conclusions: It is important for loved ones to be taken seriously in their sorrows, to be informed, that the caregivers respect the patients' will and to be emotionally supported. Trial registration number: This study was registered at the German Clinical Trials Register (DRKS00013916).
CRIS-Team Scopus Importer:2020-12-11
Keywords: hospital care; quality of life; service evaluation; social care; supportive care; terminal care